Magnetohydrodynamics evolution of three-dimensional magnetic null in NOAA active region 11515 initiated using non-force-free field extrapolation - Kumar, Sanjay; Prasad, Avijeet; Sarkar, Ranadeep; Bhattacharyya, Ramit (Frontiers in Astronomy and Space Sciences, 2022)
Magnetohydrodynamics simulation of active region NOAA 11515 is performed to examine the initiation of the M5.6 flaring event that starts around 10:43 UT on 2012 July 2. The simulation is conducted using an extrapolated non-force-free magnetic field generated from the photospheric vector magnetogram of the active region as the initial magnetic field. The magnetic field shows the presence of a three-dimensional (3D) magnetic null with the corresponding dome overlying a filament and a low-lying magnetic flux rope, observed in 304~Å~ and 131~Å~ respectively. The simulated dynamics, triggered by the initial Lorentz force, lead to the bifurcations of the flux rope, which is similar to the observed bifurcation in the 131 Å~ brightenings. Additionally, the rope exhibits a rise and reconnects at the 3D null. These reconnections convert field lines of the rope into the anchored outer spine of the 3D null --- explaining the occurrence of a nearby confined C-class flare. Further, the results show that the field lines of the flux rope reach the vicinity of the filament and become non-parallel to the field lines of the filament. This initiates the reconnections between the rope and the field lines of the filament --- activating the filament for the eruption. This interesting interaction of the flux rope and filament seem to contribute to the onset of the M-class flare.